Mitochondrial Uncoupling and the Reprograming of Intermediary Metabolism in Leukemia Cells - Vélez, Juliana; Hail, Numsen; Konopleva, Marina; Zeng, Zhihong; Kojima, Kensuke; Samudio, Ismael; Andreeff, Michael (Frontiers in Oncology, 2013)
Nearly 60 years ago Otto Warburg proposed, in a seminal publication, that an irreparable defect in the oxidative capacity of normal cells supported the switch to glycolysis for energy generation and the appearance of the malignant phenotype (Warburg, 1956). Curiously, this phenotype was also observed by Warburg in embryonic tissues, and recent research demonstrated that normal stem cells may indeed rely on aerobic glycolysis – fermenting pyruvate to lactate in the presence of ample oxygen - rather than on the complete oxidation of pyruvate in the Krebs cycle - to generate cellular energy (Folmes et al., 2012). However, it remains to be determined whether this phenotype is causative for neoplastic development, or rather the result of malignant transformation. In addition, in light of mounting evidence demonstrating that cancer cells can carry out electron transport and oxidative phosphorylation, although in some cases predominantly using electrons from non-glucose carbon sources (Bloch-Frankenthal et al., 1965), Warburg´s hypothesis needs to be revisited. Lastly, recent evidence suggests that the leukemia bone marrow microenvironment promotes the Warburg phenotype adding another layer of complexity to the study of metabolism in hematological malignancies. In this review we will discuss some of the evidence for alterations in the intermediary metabolism of leukemia cells and present evidence for a concept put forth decades ago by lipid biochemist Feodor Lynen, and acknowledged by Warburg himself, that cancer cell mitochondria uncouple ATP synthesis from electron transport and therefore depend on glycolysis to meet their energy demands (Lynen, 1951;Warburg, 1956).